Aspects regarding Burnout syndrome in healthcare workers with secondary education in the Republic of Moldova, during the pandemic period - Marina PODOROGHIN; Adriana PALADI (One Health & Risk Management, 2024)
Introduction. The COVID-19 pandemic has created favorable conditions for the onset and exacerbation of burnout syndrome. The aim of the research was to assess the degree of impact of burnout syndrome on mid-level medical staff during the pandemic period, as well as its determinants.